Capital structure as a determinant of firm value: A moderation analysis of firm size - Nurdin, Emillia; Awaluddin, Ishak; Abdullah, Muntu; Asni, Nur; Sari, Ika Maya (Edelweiss Applied Science and Technology, 2025)
This study examines the effect of capital structure on firm value, with firm size as a moderating variable. Using a quantitative approach, the research focuses on 29 food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020–2023, yielding 116 firm-year observations. Panel data regression alongside moderated regression analysis (MRA) was employed to test the hypotheses. The results show that capital structure positively affects firm value. However, firm size does not directly influence firm value. Notably, the interaction between capital structure and firm size exhibits a negative effect, indicating that higher leverage reduces firm value in larger firms. These findings suggest that while debt can enhance firm value through tax advantages and financial discipline, its benefits may be offset in larger firms due to market concerns over excessive leverage. The study concludes that optimal debt management must consider firm size to avoid diminishing investor confidence. Practically, this research offers insights for corporate managers and policymakers in structuring capital financing strategies aligned with firm-specific characteristics, particularly size, to enhance firm value sustainably.